Secondary distal renal tubular acidosis and sclerotic metabolic bone disease in seronegative spondyloarthropathy. Issue 3 (15th March 2022) - Agrawal, Neeti; Mahata, Rahin; Chakraborty, Partha Pratim; Basu, Kaushik
Abstract : Adults with distal renal tubular acidosis (dRTA) commonly present with hypokalaemia (with/without paralysis), nephrolithiasis/nephrocalcinosis and vague musculoskeletal symptoms. All adults with dRTA should be thoroughly evaluated for systemic diseases, certain medications and toxins. The leading cause of acquired or secondary dRTA in adults is primary Sjögren syndrome (SS); however, other collagen vascular diseases (CVDs) including seronegative spondyloarthropathy (SSpA) may at times give rise to secondary dRTA. Metabolic bone disease is often encountered in adults with dRTA, and the list includes osteomalacia and secondary osteoporosis; sclerotic metabolic bone disease is an extremely rare manifestation of dRTA. Coexistence of dRTA and sclerotic bone disease is seen in primary dRTA due to mutation in CA2 gene and acquired dRTA secondary to systemic fluorosis. Primary SS and SSpA, rarely if ever, may also lead to both secondary dRTA and osteosclerosis. Circulating autoantibodies against carbonic anhydrase II and possibly calcium sensing receptor may explain both these features in patients with CVD.